2017
DOI: 10.1002/pds.4267
|View full text |Cite
|
Sign up to set email alerts
|

Validity of cancer diagnosis in the National Health Insurance database compared with the linked National Cancer Registry in Taiwan

Abstract: Recording of cancer diagnoses and survival estimates based on these diagnosis codes in the NHI database are generally consistent with the NCR. Studies using NHI database data must pay careful attention to eligibility and record linkage; use of both sources is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 23 publications
2
79
0
Order By: Relevance
“…Fifth, the index date of HNC in the RCIPD is actually the date of application instead of date of cancer diagnosis. Previous study reported a delay of median of 15 days after cancer diagnosis was noted in the date of application in the NHIRD 28 . Nevertheless, in this study, we focused on the long-term outcome (more than 10 years).…”
Section: Discussionmentioning
confidence: 97%
“…Fifth, the index date of HNC in the RCIPD is actually the date of application instead of date of cancer diagnosis. Previous study reported a delay of median of 15 days after cancer diagnosis was noted in the date of application in the NHIRD 28 . Nevertheless, in this study, we focused on the long-term outcome (more than 10 years).…”
Section: Discussionmentioning
confidence: 97%
“…The HWDS claim data, which are managed by the Taiwan MOHW, consist of all medical records of more than 99% Taiwanese residents 22 . The diagnostic accuracy of the major diseases such as stroke, cardiovascular, and cancers was confirmed in other studies 22‐24 . The database is linked to the cancer patient data from the TCR and patient mortality from the TDR 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Individual information contained in the NHI database during 2002-2014 was encrypted utilizing the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code. e NHIRD is a large representative health care database, and its validity and clinical consistency in cancer research have been proved [16].…”
Section: Source Data and Study Populationmentioning
confidence: 99%
“…Using a unique personal encrypted identification number for each beneficiary in Taiwan, we are able to crosslink efficiently among different subsets of the NHI database. e internal linkage between each dataset is robust, and the data quality was accepted with validity in previous publications [16,17]. is population-based cohort study comprised ethnic Taiwanese patients with the main diagnosis of lung cancer (ICD-9-CM code 162.xx) identified via the NHIRD from 2002 to 2014. e histological subtypes of lung cancer were retrieved from the TCRD, while the survival rates were extracted from the NDR database.…”
Section: Source Data and Study Populationmentioning
confidence: 99%